"This weird time we're in": How a sudden change to remote education impacted college students' self-regulated learning. (31st January 2022) - Hensley, Lauren C.; Iaconelli, Ryan; Wolters, Christopher A.
Abstract: The present study investigates the impacts that a sudden change to online instruction had on undergraduates' engagement in self-regulated learning during the COVID-19 global pandemic. Using reflexive thematic analysis to examine college students' written responses, we identified four themes that illustrated the challenges of emergency remote learning: feeling disconnected, discordant, and distracted; struggling to engage amid lost autonomy and personal stressors; experiencing academic burden and burnout; and encountering both caring and disregard from instructors. The implications of these findings highlight the importance that learning contexts and social connectedness have on undergraduates' willingness and ability to enact self-regulated learning behaviors and strategies.